SEC Trading Suspensions: Empirical Evidence - Howe, John S.; Schlarbaum, Gary G. (Journal of Financial and Quantitative Analysis, 1986)
This article explores the price behavior of a sample of corporate securities in which trading was temporarily suspended by the SEC. Suspensions are found to coincide with substantial devaluations of the suspended securities. Further, significant and prolonged negative abnormal returns are observed in the postsuspension period, an apparent violation of semistrong form market efficiency.